Professional sheet metal fabrication - Barr, Ed (Minneapolis, Minnesota : Motorbooks, 2013)
Professional Sheet Metal Fabrication is the number-one resource for sheet metal workers old and new. Join veteran metalworker Ed Barr as he walks you through the ins and outs of planning a sheet metal project, acquiring the necessary tools and resources, doing the work, and adding the perfect finishing touches for a seamless final product. From his workshop at McPherson College--home of the only genuine sheet metal.
Getting Started -- Special Techniques for Welding Sheet Metal -- Brazing, Soldering, and Riveting -- Cutting Sheet Metal with the Oxyacetylene Torch and Plasma Cutter -- Beginning Sheet Metal Shaping -- The Small Gas Tank Project -- Advanced Sheet Metal Shaping -- Building a fender from Concept to Completion -- Making It Beautiful: Straightening, Grinding, and Surface Finishing -- Building a Custom Pedal Car -- Floorpans, Rocker Panels, and Rear Quarter Panels -- Repairing Doors -- Repairing Fenders, hoods, and Trunk Lids.
Includes bibliographical references and index.
Keywords: AUTOMOBILES -- BODIES